Addictive Behavior in Immigrant Psychiatric Inpatients: the Immigrant Paradox Failure (Zdravstveni glasnik, 2024)
INTRODUCTION: In the last years migration has become a major political and social concern in West-Europe. Some researchesindicate that immigrants are more prone to certain psychiatric disorders, while other show the “immigrant paradox”.Data about immigrants’ admission to acute psychiatry settings and substances and alcohol use-related considerations are still controversial.AIMS: To evaluate data about immigrants’ admission to the acute Italian Psychiatry Ward of Hospital of Novara, focusing on substances and alcohol.METHODS: The study was performed from January to December 2017, without any exclusion criteria. The final database contains detailed information including diagnostic treatment-related and sociodemographic characteristics. The sample was divided into two subgroups: immigrants with (SAU) or without a history of substances or alcohol abuse (N-SAA). Each patient was assessed with the Health of the Nation Outcome Scales and the Clinical Global Impression. RESULTS: Of the total of 71 immigrants (mean age 37.95 years), 34 were female.49.3% of them with SAU. Specifically, immigrants with SAU seemed to have a shorter hospital stayand to obtain higher scores on the subscale “behavior” and “social” of HONOS(p